A Silver Complex with Cycloserine: Synthesis, Spectroscopic Characterization, Crystal Structure and In Vitro Biological Studies - Ciol, Mariana Rosolen; Manzano, Carlos Marrote; Cuin, Alexandre; Pavan, Fernando Rogério [UNESP]; Ribeiro, Camila Maríngolo [UNESP]; Ruiz, Ana Lúcia Tasca Gois; de Oliveira, Ellen Cristina S.; Lustri, Wilton Rogério; Fregonezi, Nathália Ferreira; Nogueira, Flávia Aparecida Resende; Corbi, Pedro P. (Wiley, 2018)
Synthesis, characterization and biological activities of a silver(I) complex with cycloserine (AgCIC) are presented. Elemental, thermal and mass spectrometric analyses permitted proposing the minimal formula AgC3H5N2O2. The structure of the AgCIC complex was solved by powder X-ray diffraction (XRD) studies. Coordination of the ligand to silver was shown to occur by the nitrogen atom of the heterocyclic ring and by the nitrogen and oxygen atoms of the amino and carbonyl groups, leading to a polymeric arrangement. Infrared (IR) and nuclear magnetic resonance (NMR) spectroscopic analyses confirmed the coordination sites. Antibacterial assays revealed the activity of the AgCIC complex against Mycobacterium tuberculosis, with minimal inhibitory concentration (MIC90) of 79.1 μmol⋅L−1, and against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa bacterial strains. Antiproliferative assays over a panel of tumoral and non-tumoral cells showed that the AgCIC complex is more active and selective than doxorubicin against breast and leukemia cancer cells, considering the total growth inhibition (TGI) values. The interaction of the complex with biomolecules and its mutagenicity were also investigated.
Keywords: antimycobacterial agents; antitumor activities; crystal structure; cycloserine; silver